2021
DOI: 10.1038/s41572-021-00269-y
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer disease

Abstract: Competing interests D.S.K. served on a Data Safety Monitoring Board for the DIAN study. He serves on a Data Safety Monitoring Board for a tau therapeutic for Biogen but receives no personal compensation. He is a site investigator in a Biogen aducanumab trial. He is an investigator in a clinical trial sponsored by Lilly Pharmaceuticals and the University of Southern California. He serves as a consultant for Samus Therapeutics, Third Rock, Roche and Alzeca Biosciences but receives no personal compensation. He re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
842
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,134 publications
(1,082 citation statements)
references
References 289 publications
8
842
2
9
Order By: Relevance
“…Currently, there are 44 million people dealing with dementia, being the second leading cause of death in people aged 70 and over [1][2][3][4]. Alzheimer's disease (AD) is the most prevalent form of dementia [1] and it is also one of the most significant causes of morbidity and mortality in the elderly population worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are 44 million people dealing with dementia, being the second leading cause of death in people aged 70 and over [1][2][3][4]. Alzheimer's disease (AD) is the most prevalent form of dementia [1] and it is also one of the most significant causes of morbidity and mortality in the elderly population worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is the most prevalent form of dementia [1] and it is also one of the most significant causes of morbidity and mortality in the elderly population worldwide [3]. AD prevalence is estimated to reach Pharmaceuticals 2021, 14, 890 2 of 22 115 million by 2050 due to an increased ageing population pattern, unless novel drugs are available to slow or cure this disease [2][3][4]. Neuropathological modifications of AD, such as tau hyperphosphorylation and Aβ toxicity, led to the main current hypothesis trying to explain neuronal and synapse loss, associated with cognitive and memory impairment [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical diagnosis of AD is based on the presence of objective cognitive deficits (which are, typically, prominent memory impairments). In some cases, AD may show atypical presentations, with impairments in non-amnesic domains (i.e., attention, executive functions, visuo-constructive practice and language) [1]. However, AD shares many common clinical features with other neurodegenerative dementia, including Lewy body dementia [2], frontotemporal disorders [3], and vascular dementia, making early and differential diagnosis difficult, especially in the first stage of the disease [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of AD remains unclear, a large number of clinical and preclinical experiments have shown that the occurrence and development of AD were closely related to Aβ toxic injury, abnormal phosphorylation of tau protein, inflammatory reaction, free radical damage, and so on (Chiti and Dobson, 2017;Li et al, 2018). According to the preliminary studies, the pathogenesis of AD was mainly related to Aβ plaques, but the therapeutic strategies aimed at reducing β-amyloid protein failed one after another (Loureiro et al, 2020;Knopman et al, 2021). Similarly, there was no breakthrough in the study on the phosphorylation of tau protein (Hane et al, 2017;Morris et al, 2018).…”
Section: Introductionmentioning
confidence: 99%